Cleft Lip and Palate in a Patient with 5q35.2-q35.3 Microdeletion: The Importance of Chromosomal Microarray Testing in the Craniofacial Clinic. (September 2013) - Peredo, Jane; Quintero-Rivera, Fabiola; Bradley, James P.; Tu, Marinda; Dipple, Katrina M.
We report on a 3½-year-old African American female with a 1.63 Mb microdeletion in 5q35.2-q35.3. This deletion includes NSD1, the gene that causes Sotos syndrome. The patient has unilateral cleft lip and palate (CLP) status postrepair, an unrepaired alveolar cleft, speech delay, global developmental delay, macrocephaly, mild cerebral palsy, and a patent ductus arteriosus status postrepair. Dysmorphic features include a prominent forehead and midface hypoplasia. This is one of the first cases of CLP associated with Sotos syndrome and emphasizes the utility of chromosomal microarray analysis in patients with more than isolated CLP in the Craniofacial Clinic.